New ideas and framework for combating COVID-19 pandemic using IoT technologies - Hussein M. Haglan; Akeel Sh. Mahmoud; Mustafa Hamid Al-Jumaili; Ahmed J. Aljaaf (Institute of Advanced Engineering and Science, 2021)
The internet of things (IoT) is one of the most advanced technologies that have emerged in the last decade. In recent years, IoT has been used in many medical fields. With the emergence of the Coronavirus pandemic, some IoT technologies were employed to serve the health sector to make quick and accurate decisions to save people's lives. However, there are still many ideas and works not yet implemented that could be applied in many aspects to preserve people's lives. Therefore, it is necessary to collect works and ideas that depend on IoT to produce modern systems quickly to serve the health sector. In this paper, a review of the most recent technologies of IoT against Coronavirus disease (COVID-19) has been done. A comparative and analysis among the previous works have been done to reach the most efficient depending on comparing the services that each work has provided. Besides that, suggest several new ideas that can be adopted as systems use IoT technologies and the expected advantages that can be gain from applying these ideas. A framework for a proposed idea to build a comprehensive monitoring system based on IoT technologies on the patient and hospital sides and expected advantages of implementing the system has been done.